(untitled) (Communication & Society, 2022)
During lockdown, as a consequence of the coronavirus crisis in 2020, the majority of Spanish people (70% of social media users) were exposed to a social media consumer space: news without journalistic filters, with a multitude of fake data and a systematic existence of misinformation that has had a close relationship with the perception of credibility. 1,000 surveys were conducted between March 30 and April 30, in Spain. This work describes the consumption patterns of political parties in social networking sites, describing the facts that determine to what extent Spanish people trust the news they receive. The amount of information consumed online, age and the party identification with Vox and Ciudadanos are the most relevant communicative, structural or political variables that explain the increase or decrease in the credibility of the information that Spaniards receive through these channels.